Censorship detected in IT (Italy) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in Italy. Data sourced from CensoredPlanet.
Censorship Incident ID: IT-2026-0003. Severity: warning. Confidence: 65%